Role of distinct dimorphic transitions in territory colonizing and formation of yeast colony architecture - Vopálenská, Irena; St'ovícek, Vratislav; Janderová, Blanka; Váchová, Libuse; Palková, Zdena (Environmental microbiology, 2010)
Microbial populations in nature often form organized multicellular structures (biofilms, colonies) occupying different surfaces including host tissues and medical devices. How yeast cells within such populations cooperate and how their dimorphic switch to filamentous growth is regulated are therefore important questions. Studying population development, we discovered that Saccharomyces cerevisiae microcolonies early after their origination from one cell successfully occupy the territory via dimorphic transition, which is induced by ammonia and other volatile amines independently on cell ploidy and nutrients. It results in oriented pseudohyphal cell expansion in the direction of ammonia source, which consequently leads to unification of adjacent microcolonies to one more numerous entity. The further population development is accompanied by another dimorphic switch, which is strictly dependent on Flo11p adhesin and is indispensable for proper formation of biofilm-like aerial 3-D colony architecture. In this, Flo11p is required for both elongation of cells organized to radial clusters (formed earlier within the colony) and their subsequent pseudohyphal expansion. Just before this expansion, Flo11p relocalizes from the bud-neck of radial cell clusters also to the tip of elongated cells.
Keywords: kultivační média; hyfy; Hyphae; Saccharomyces cerevisiae; Mutation; amoniak; Membrane Glycoproteins; regulace genové exprese u hub; Ammonia; Culture Media; Saccharomyces cerevisiae Proteins; delece genu; Saccharomyces cerevisiae - proteiny; membránové glykoproteiny; Gene Expression Regulation, Fungal; mutace; Gene Deletion